UPAYA PENINGKATAN PENDAPATAN USAHATANI SAYURAN MELALUI PEMBUATAN PUPUK ORGANIK DI DESA PENFUI TIMUR, KABUPATEN KUPANG - Suek, Johanna; Surayasa, Made Tusan; Suryatni, Putu Febri; Siubelan, Yacobus C.W, (Jurnal Abdi Insani, 2024)
Increasing income in vegetable farming through the use of organic fertilizers as an alternative to the use of inorganic fertilizers has become increasingly prevalent. The limited capital owned, as well as the availability of animal and plant organic materials around farmers, are valuable potentials for making organic fertilizers. This activity aims to conduct counseling, manufacture, and use of organic fertilizers on vegetable farms to increase farmers' income.  Activities were carried out in a participatory manner at the location of Rukun Tetangga 30 and Bethesda Farmers Group in two training periods. The training target is to increase the knowledge and skills of the partner community. The results of participatory training obtained community knowledge about the function of organic fertilizer, how to make it increase, and how to apply it to vegetable increase. The profit earned from one time making organic fertilizer is Rp. 658,000. There was an increase in vegetable production in response to the application of organic fertilizer by 10-20%, and additional income increased by 20%.